Measuring Elaboration and Evaluating Its Influence on Behavioral Intentions. Issue 1 (April 2018) - Miller, Zachary D.; Freimund, Wayne; Powell, Robert B.
The focus of this study is on developing a scale that measures elaboration as originally conceptualized by Vezeau et al. (2015), and then tests whether the elaboration scale is able to predict a variety of related behaviors. Confirmatory factor analysis was used to investigate the validity and reliability of the scale. The results suggest that the scale was successful in improving upon previous research in that all theoretical constructs were present in the second-order model of elaboration. Additionally, structural equation modeling was used to examine the predictive validity of the elaboration scale, which was successful in predicting a variety of related behaviors. This research advances the theoretical understanding and measurement of elaboration. Results can be used for evaluating interpretation efforts, including the assessment of programs and materials. Additionally, the results provide further evidence of elaboration as a measured construct and opens a variety of new avenues for research in environmental interpretation and informal education. Practitioners can use this research to reinforce or change attitudes and behaviors of visitors to those more consistent with an agency or organization mission by promoting interest, awareness, and cognitive engagement (collectively termed elaboration ) in their interpretive products.